Simple voting games and cartel damage proportioning - Stefan Napel; Dominik Welter (Games, 2021)
Individual contributions by infringing firms to the compensation of cartel victims must reflect their 'relative responsibility for the harm caused' according to EU legislation. Several studies have argued that the theoretically best way to operationalize this norm is to apply the Shapley value to an equilibrium model of cartel prices. Because calibrating such a model is demanding, legal practitioners prefer workarounds based on market shares. Relative sales, revenues, and profits however fail to reflect causal links between individual behavior and prices. We develop a pragmatic alternative: use simple voting games to describe which cartel configurations can(not) cause significant price increases in an approximate, dichotomous way; then compute the Shapley-Shubik index. Simulations for a variety of market scenarios document that this captures relative responsibility better than market share heuristics can.
Keywords: C71; D04; L40; L13; D43; 330; cartel damage allocation; relative responsibility; Shapley-Shubik index; simple voting games